A study of patients’ satisfaction with the Emergency Department (ED) of Hospital Universiti Kebangsaan Malaysia (HUKM) - Ismail Saiboon; Ho, Siew Eng; Bala Krishnan; Siti Nooraini Ali; Noorafindi Murad; Audrey Pathnathan; Yin, Choy Choy (Penerbit UKM, 2008)
Patients’ satisfaction is of critical interest to all healthcare providers. Satisfied patients are more likely to seek health care and to comply with prescribed treatment regimes. The objective of the study was to identify factors that influence patient satisfaction with Emergency Department HUKM (ED HUKM). This study was conducted at ED HUKM from January 2007 till March 2007. A convenience sample of 100 participants was recruited from triage 4. The Davis Consumer Emergency Care Satisfaction Scale (CECSS) was adopted and modified. It consists of 19 questions; used a 5 point, Likert type scale of 1 to 5 (1= completely disagree and 5= completely agree) to measure patient satisfaction with triage, health care providers caring behaviours and health teaching. Results showed that 75 participants (75%) were satisfied. There were no significant difference found between male and female patients with total CESCC scores (t=0.308, p values >0.05). Pearson product moment correlation coefficients showed a positive relationship between total and subscale patient satisfaction scores, caring scores (r=0.905, p value <0.05) and teaching scores (r=0.695, p < 0.05). Overall, patients were satisfied with services at the ED HUKM. Patients’ satisfaction remains as an important quality outcome measure of emergency care in any hospital